COHORT PROFILE: THE PRECIPITATING EVENTS PROJECT (PEP STUDY) - GILL, T.M. (J Nutr Health Aging, 2020)
The Precipitating Events Project (PEP Study) is an ongoing longitudinal study of 754 nondisabled community-living persons age 70 years or older who were members of a large health plan in greater New Haven, Connecticut, USA. The study was established to rigorously evaluate the epidemiology of disability in older persons and to elucidate the role of intervening illnesses and injuries on the disabling process. Of the eligible members, 75.2% agreed to participate and were enrolled between March 1998 and October 1999. Participants have completed comprehensive home-based assessments at 18-month intervals and have been interviewed monthly over the phone with a completion rate of 99%. Detailed participant-level data on health care utilization are obtained annually through linkages with Medicare claims. Through June 2019, 702 (93.1%) participants have died after a median of 109 months, while 43 (5.7%) have dropped out of the study after a median of 27 months. Death certificates are available for all decedents. To date, 117 original reports have been published using data from the PEP Study, including many focusing on other high priority areas such as end of life, frailty, depressive symptoms, aging stereotypes, pain, sleep, and methodologic research. The PEP Study welcomes proposals to access data for meritorious analyses from qualified investigators.